Revisiting German labour market reform effects: A panel data analysis for occupational labour markets - Michael Stops (IZA Journal of European Labor Studies, 2016)
The role of the 2000's German labour market reforms in boosting the German economy has been widely discussed. Considering that one of the main objectives of these reforms was to improve the matching process on the labour market, I use high-frequency administrative data to present new details regarding the development of job-matching performance from 2000 to 2011. Matching productivity increased during all reform stages. Increases in matching productivity have become smaller from 2009. The analysis shows also differences and commonalities in the matching productivity changes on occupational labour markets.
Keywords: C23; J44; J64; 330; Labour market reforms; Unemployment; Vacancies; Matching model; Panel data; Occupational labour markets